Prevalence of Hypertension and Associated Risk Factors in Western Alaska Native People: The Western Alaska Tribal Collaborative for Health (WATCH) Study. Issue 10 (3rd February 2015) - Jolly, Stacey E.; Koller, Kathryn R.; Metzger, Jesse S.; Day, Gretchen M.; Silverman, Angela; Hopkins, Scarlett E.; Austin, Melissa A.; Boden‐Albala, Bernadette; Ebbesson, Sven O. E.; Boyer, Bert B.; Howard, Barbara V.; Umans, Jason G.
<x xml:space="preserve">Abstract</x> Hypertension is a common chronic disease and a key risk factor in the development of cardiovascular disease. The Western Alaska Tribal Collaborative for Health study consolidates baseline data from four major cohorts residing in the Norton Sound and Yukon‐Kuskokwim regions of western Alaska. This consolidated cohort affords an opportunity for a systematic analysis of high blood pressure and its correlates in a unique population with high stroke rates over a wide age range. While the prevalence of hypertension among western Alaska Native people (30%, age‐standardized) is slightly less than that of the US general population (33%), cardiovascular disease is a leading cause of mortality in this rural population. The authors found that improvement is needed in hypertension awareness as about two thirds (64%) of patients reported awareness and only 39% with hypertension were controlled on medication. Future analyses assessing risk and protective factors for incident hypertension in this population are indicated.